2019
DOI: 10.3390/geosciences9040189
|View full text |Cite
|
Sign up to set email alerts
|

First Identification of Periodic Degassing Rhythms in Three Mineral Springs of the East Eifel Volcanic Field (EEVF, Germany)

Abstract: We present a geochemical dataset acquired during continual sampling over 7 months (biweekly) and 4 weeks (every 8 hours) in the Neuwied Basin, a part of the East Eifel Volcanic Field (EEVF). We used a combination of geochemical, geophysical, and statistical methods to identify potential causal processes underlying the correlations of degassing patterns of four gases (He, Rn, CO 2 , O 2 ), earth tides, and tectonic processes in three mineral springs (Nette, Kärlich and Kobern). We explored whether temporal rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…Although beyond the scope of this review, we highlight that periodicity in volcanic gas emissions can also be manifest in timeseries of regional diffuse degassing. Berberich et al [123] identified periodic fluctuations in degassing from mineral springs in the East Eifel Volcanic Field, Germany, on timescales of 1 day (solar diurnal cycle), 4-6 days and 10-15 days, which they suggested reflected either variations in the deep gas source, changes in the transport pathway for gases to reach the surface, or the influence of volcano-tectonic earthquakes. Soil degassing (predominantly CO 2 ) can also provide good indications of the onset of volcanic unrest and magma movement at depth [124], although such datasets can also be sensitive to environmental and climatic influences [125,126]; for example, 47% of the soil CO 2 flux variations at Fogo, Azores, could be explained by the effect of the soil and air temperature, wind speed, and soil water content [127].…”
Section: Periodicity In Magma Storage Region (C4)mentioning
confidence: 99%
“…Although beyond the scope of this review, we highlight that periodicity in volcanic gas emissions can also be manifest in timeseries of regional diffuse degassing. Berberich et al [123] identified periodic fluctuations in degassing from mineral springs in the East Eifel Volcanic Field, Germany, on timescales of 1 day (solar diurnal cycle), 4-6 days and 10-15 days, which they suggested reflected either variations in the deep gas source, changes in the transport pathway for gases to reach the surface, or the influence of volcano-tectonic earthquakes. Soil degassing (predominantly CO 2 ) can also provide good indications of the onset of volcanic unrest and magma movement at depth [124], although such datasets can also be sensitive to environmental and climatic influences [125,126]; for example, 47% of the soil CO 2 flux variations at Fogo, Azores, could be explained by the effect of the soil and air temperature, wind speed, and soil water content [127].…”
Section: Periodicity In Magma Storage Region (C4)mentioning
confidence: 99%
“…Berberich et al [28] provide a more complete geological, tectonic, and volcanological description of the Goloring study site. Our Goloring study site is situated in the center of a triangle-shaped study area formed by the three previously-investigated mineral springs (Flöcksmühle in the Nette river near Ochtendung [hereafter: ‘Nette’], Waldmühle in Mülheim-Kärlich [hereafter: ‘Kärlich’] and ‘Kobern’ in Kobern-Gondorf (Figure 2a; [35]). No fault zones had been reported and identified previously from the Goloring study site; local earthquakes magnitude never exceeded M L = 2, and focal depths of earthquakes near it never exceeded 28 km during our sampling campaign [37].…”
Section: Methodsmentioning
confidence: 99%
“…We measured gases in ambient air (AA), soil (SG; Figure 2d), and the RWA nest (NG) at the Iron age henge sanctuary at the Goloring site (Figure 2b) biweekly from 1 March–30 September 2016 (7-M; 16 times) and every eight hours between 12 July and 11 August 2016 (4-W; 83 times), yielding a total of 2673 gas samples. Gas sampling followed procedures described by Berberich [24] using analytical equipment and sampling methods described by Berberich et al [28,35]. Briefly, AA was sampled at 1 m height, 1 m away from the RWA nest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations